Alpha-synuclein interacts with regulators of ATP homeostasis in mitochondria - Tetiana Serdiuk; Yanick Fleischmann; Dhiman Ghosh; Aro Delparente; Viviane Reber; Larissa Frey; David Rhyner; Juan Gerez; Norbert Volkmar; Lucie Kralickova; Guillaume Mas; Christian Dörig; et al. (Nature Communications)
Abstract Mitochondrial dysfunction and accumulation of α-synuclein aggregates are hallmarks of the neurodegenerative Parkinson’s disease and may be interconnected. To investigate the interplay between α-synuclein and brain mitochondria at near atomic structural level, we apply NMR and identify α-synuclein protein interactors using limited proteolysis-coupled mass spectrometry (LiP-MS). Several of the proteins identified are related to ATP synthesis and homeostasis and include subunits of ATP synthase and the adenylate kinase AK2. Furthermore, our data suggest that α-synuclein interacts with the Parkinson’s disease-related protein DJ1. NMR analysis demonstrates that both AK2 and DJ1 bind to the C-terminus and other segments of α-synuclein. Using a functional assay for AK2, we show that monomeric α-synuclein has an activating effect, whereas C-terminally truncated α-synuclein and α-synuclein in an amyloid fibrillar state have no significant effect on AK2 activity. Our results suggest that α-synuclein modulates ATP homeostasis in a manner dependent on its conformation and its C-terminal acidic segment.